Invariant NKT Cell-Mediated Modulation of ILC1s as a Tool for Mucosal Immune Intervention - Trittel, Stephanie; Vashist, Neha; Ebensen, Thomas; Chambers, Benedict J.; Guzmán, Carlos A.; Riese, Peggy (Frontiers in Immunology, 2019)
Non-NK group 1 innate lymphoid cells (ILC1s), mainly investigated in the mucosal areas of the intestine, are well known to contribute to anti-parasitic and anti-bacterial immune responses. Recently, our group revealed that lung ILC1s become activated during murine influenza infection, thereby contributing to viral clearance. In this context, worldwide seasonal influenza infections often result in severe disease outbreaks leading to high morbidity and mortality. Therefore, new immune interventions are urgently needed. In contrast to NK cells, the potential of non-NK ILC1s to become functionally tailored by immune modulators to contribute to the combat against mucosal-transmitted viral pathogens has not yet been addressed. The present study aimed at assessing the potential of ILC1s to become modulated by iNKT cells activated through the CD1d agonist αGalCerMPEG. Our results demonstrate an improved functional responsiveness of murine lung and splenic ILC1s following iNKT cell stimulation by the mucosal route, as demonstrated by enhanced surface expression of TRAIL, CD49a and CD28, and increased secretion of IFNγ. Interestingly, iNKT cell stimulation also induced the expression of the checkpoint molecules GITR and CTLA-4, which represent crucial points of action for immune regulation. An in vivo influenza infection model revealed that intranasal activation of ILC1s by αGalCerMPEG contributed to increased viral clearance as shown by reduced viral loads in the lungs. The findings that ILC1s can become modulated by mucosally activated iNKT cells in a beneficial manner emphasize their up to now underestimated potential as targets in novel immune interventions against influenza and other respiratory infections.